2017
DOI: 10.1007/s10658-017-1190-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Alternaria species causing leaf spot on cabbage, cauliflower, wild and cultivated rocket by using molecular and morphological features and mycotoxin production

Abstract: Alternaria species are common pathogens of fruit and vegetables able to produce secondary metabolites potentially affecting human health. Twenty-nine isolates obtained from cabbage, cauliflower, wild and cultivated rocket were characterized and identified based on sporulation pattern and virulence; the phylogenetic analysis was based on the β-tubulin gene. Isolates were identified as A. alternata, A. tenuissima, A. arborescens, A. brassicicola and A. japonica. Pathogenicity was evaluated on plants under greenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…All 12 Alternaria spp. ( A. alternata , A. arborescens , A. brassicae , A. conjuncta , A. ethzedia , A. eureka , A. hordeicola , A. infectoria , A. japonica , A. malvae , A. metachromatica and A. tenuissima ) reported in the current study have been associated with alternaria leaf spot either within or outside Australia on one or more Brassicaceae or non‐Brassicaceae hosts (Sampson & Walker, ; Shivas, ; Fisher et al ., ; You et al ., , ; Mułenko et al ., ; Garibaldi et al ., ; Sharma et al ., ; Bassimba et al ., ; Harteveld et al ., ; Lee et al ., ; Bashir et al ., ; Barkat et al ., ; Taj et al ., ; Van de Wouw et al ., ; Atlas of Living Australia, ; APPD, ; Farr & Rossman, ; Moslemi et al ., ; Siciliano et al ., ). It is evident that leaf spotting on canola in Australia is not soley caused by a single widely recognized Alternaria species such as A. brassicae , but that a range of up to nine other Alternaria spp.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…All 12 Alternaria spp. ( A. alternata , A. arborescens , A. brassicae , A. conjuncta , A. ethzedia , A. eureka , A. hordeicola , A. infectoria , A. japonica , A. malvae , A. metachromatica and A. tenuissima ) reported in the current study have been associated with alternaria leaf spot either within or outside Australia on one or more Brassicaceae or non‐Brassicaceae hosts (Sampson & Walker, ; Shivas, ; Fisher et al ., ; You et al ., , ; Mułenko et al ., ; Garibaldi et al ., ; Sharma et al ., ; Bassimba et al ., ; Harteveld et al ., ; Lee et al ., ; Bashir et al ., ; Barkat et al ., ; Taj et al ., ; Van de Wouw et al ., ; Atlas of Living Australia, ; APPD, ; Farr & Rossman, ; Moslemi et al ., ; Siciliano et al ., ). It is evident that leaf spotting on canola in Australia is not soley caused by a single widely recognized Alternaria species such as A. brassicae , but that a range of up to nine other Alternaria spp.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Siciliano et al . () found that all tested isolates of A. alternata , A. arborescens , A. brassicicola , A. japonica and A. tenuissima were pathogenic across different hosts in the family of Brassicaceae; while Farr & Rossman () reported A. ethzedia on B. napus in Switzerland, A. hordeicola on Hordeum vulgare in Norway and A. malvae on Malva sinensis in China. Furthermore, alternaria leaf spotting caused by A. conjuncta has been recorded on Daucus carota in Poland (Mułenko et al ., ), A. infectoria on Malus domestica in South Africa (Farr & Rossman, ), A. metachromatica on Solanum lycopersicum in Pakistan (Bashir et al ., ), A. tenuissima on Farfugium japonicum in Korea (Lee et al ., ), and Cajanus cajan in India (Sharma et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Siciliano et al . () found three distinct virulences for A. alternata on cultivated rocket (high, moderate, and low virulence) and two distinct of virulences for A. japonica on wild rocket (high and moderate virulence). Finally, variability in virulence has also been demonstrated in A. alternata , A. brassicicola , and A. raphani on Brassicaceae in other studies (Atkinson, ; Stoll, ; Czyżewska, ; Nowakowska et al .…”
Section: Discussionmentioning
confidence: 99%